2021
DOI: 10.7759/cureus.20021
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic on Obsession and Compulsion Symptoms in Saudi Arabia

Abstract: BackgroundObsessive-compulsive disorder (OCD) is a common condition that has a significant impact on people's lives. COVID-19 pandemic imposed a challenging situation for the general population with new precautionary measures. All that can have serious implications for those who already have intense concerns about cleanliness and hygiene and those diagnosed with OCD. The aim of this study was to examine the impact of the coronavirus disease 2019 (COVID-19) pandemic on the emergence and severity of obsession an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
(29 reference statements)
1
10
0
Order By: Relevance
“…Increased behavioral dysregulation, anger and irritability during the pandemic have been described in children and adolescents during the pandemic (Mohler-Kuo et al 2021 ; see Panchal et al 2021 ), often in interaction with enhanced parental stress (Andrés et al 2022 ; Montirosso et al 2021 ). Referrals for OCD, eating disorders, behavioral addictions and substance had also increased, in agreement with studies on pandemic effects on eating disorders (Otto et al 2021 ; Schwartz and Costello 2021 ), OCD (Alhujaili et al 2021 ; Sowmya et al 2021 ), substance use disorder (Sen et al 2021 ), problematic digital media use (Masaeli and Farhadi 2021 ). The number of participants who indicate frequent referrals for problematic use of the internet/problematic gaming has more than doubled during the pandemic.…”
Section: Discussionsupporting
confidence: 71%
“…Increased behavioral dysregulation, anger and irritability during the pandemic have been described in children and adolescents during the pandemic (Mohler-Kuo et al 2021 ; see Panchal et al 2021 ), often in interaction with enhanced parental stress (Andrés et al 2022 ; Montirosso et al 2021 ). Referrals for OCD, eating disorders, behavioral addictions and substance had also increased, in agreement with studies on pandemic effects on eating disorders (Otto et al 2021 ; Schwartz and Costello 2021 ), OCD (Alhujaili et al 2021 ; Sowmya et al 2021 ), substance use disorder (Sen et al 2021 ), problematic digital media use (Masaeli and Farhadi 2021 ). The number of participants who indicate frequent referrals for problematic use of the internet/problematic gaming has more than doubled during the pandemic.…”
Section: Discussionsupporting
confidence: 71%
“…Although the wellbeing and emotional resilience of healthcare professionals are key components of continuing healthcare services during the COVID-19 pandemic, healthcare professionals have been observed in this period to experience serious psychological problems and to be at risk in terms of mental health 15 . Various studies among frontline physicians, nurses, paramedical and administrative staff around the world, revealed a high prevalence of stress, anxiety and depression 16,17 We found that the overall subjective wellbeing and meaning in life scores are noticeably higher for the American participants whereas the fear of COVID-19 and resilience scores are close in both studies, with slightly higher resilience and lower fear in the Israeli HCWs. This difference may be explained by the Israeli geo-political-social context, related to the potential of persistent and pervasive threat and risk exposure, which may influence the perception of resilience and result in effective coping strategies of the Israeli cohort 18,19.…”
Section: The Differences Between the Two Cohortsmentioning
confidence: 58%
“…15 In Suadi Arabia and other Middle Eastern countries, the prevalence of OCD symptoms meeting clinical diagnosis was estimated at 2.8% )ranging between 0.1% to 12.2%(, 17,18 where symptoms are associated with a significant negative impact on social activities and quality of life. [19][20][21] Local studies focusing on OCD symptoms during the pandemic are limited in number and scope, [22][23][24] the studies primarily focused on contamination and cleaning aspects of OCD symptoms 22 and did not include targeted COVID-19 patients or a focus on the more comprehensive and exhaustive OCD symptoms. 23,24 Therefore, a gap in literature exists on the link between COVID-19 infection and the development of comprehensive OCD symptoms in Saudi Arabia.…”
mentioning
confidence: 99%
“…After conducting a thorough web based research, previous studies confirmed a wide variability in the prevalence of OCD symptoms among the general population during the COVID-19 pandemic. [22][23][24][25][26][27][28] Assuming a symptoms frequency of 35% with two-sided confidence limits of 5%, a sample size of 350 patients was estimated, using an 80% power level and 95% two-sided significance level.…”
mentioning
confidence: 99%
See 1 more Smart Citation